2007
DOI: 10.2320/matertrans.mj200752
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Indenter Geometry on the Deformation Behavior of Zr<SUB>60</SUB>Cu<SUB>30</SUB>Al<SUB>10</SUB> Bulk Metallic Glass during Nanoindentation

Abstract: As a first step in examining a new aspect of inhomogeneous plastic flow in bulk metallic glasses (BMGs) during nanoindentation, a series of nanoindentation experiments were performed on Zr 60 Cu 30 Al 10 BMG with two pyramidal indenters (Berkovich and cube-corner indenters) having different centreline-to-face angle. It was revealed that the indenter angle can be a new controllable factor affecting the serrated flow behaviour of the BMG during nanoindentation, since a sharper cube-corner indenter induces differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
1
6
1
Order By: Relevance
“…8(d) as an example). The literature reports that an increased number of discrete bursts, or pop-ins, visible in the P-h curve corresponds not only to more pronounced shear banding activity but also this generally results in more shear bands reaching the surface near nano-indents [38,39]. However, this is not the case in the present study.…”
Section: J/cmcontrasting
confidence: 71%
“…8(d) as an example). The literature reports that an increased number of discrete bursts, or pop-ins, visible in the P-h curve corresponds not only to more pronounced shear banding activity but also this generally results in more shear bands reaching the surface near nano-indents [38,39]. However, this is not the case in the present study.…”
Section: J/cmcontrasting
confidence: 71%
“…For example, Schuh et al [183] showed that increasing T leads to the gradual emergence of homogeneous flow, as thermal relaxations allow dissipation of strain localization into general viscous flow. Another critical factor is the indenter angle [184]; as shown in Fig. 13, sharper the indenter, more pronounced are the popin events.…”
Section: Discrete Deformation During Nanoindentationmentioning
confidence: 95%
“…For example, shear bands can be observed on the surface around hardness impression, which is clearer when indentations are made with a sharper indenter [181]. However, imaging the entire shape of shear bands development, to develop 'structureproperty' correlations, is difficult since most of the shear bands usually form underneath the indenter and do not manifest often on to the free surface [184]. To overcome this, the 'bonded interface' technique, which was pioneered by Mulhearn and Van Der Zwaag et al for metals and brittle materials, respectively [193,194], was utilized to study the subsurface deformation characteristics (especially, the shear band patterns) in a plane along the indentation axis [195][196][197][198][199][200][201][202][203].…”
Section: Plasticity Evolution and Pressure Sensitivitymentioning
confidence: 99%
“…31,35 Flow serration in nanoindentation load-displacement curves is observed to be sensitive to composition, processing history, tip shape, applied loading rate, and temperature. 31,[36][37][38][39][40][41][42][43][44] The shear band corresponding to the initial yield event in low-load spherical indentation does not originate from the point of maximum shear stress in the Hertzian field (located at a distance of roughly half a contact radius into the material 26,40 ), but instead is believed to span a trajectory ranging from the edge of the contact to a depth greater than twice the contact radius. 9 Two considerations enter into our expectations about the NSD of metallic glasses.…”
Section: Nsd In Amorphous Metalsmentioning
confidence: 99%